Big Blue's big bet. (Economist, 2000)
Reports on research at the IBM Thomas J. Watson research center in Yorktown Heights, New York on building a powerful computer called Blue Gene. Intention for the supercomputer to help biologists explore how proteins fold themselves into their distinctive shapes; Problems in parallel computing; Details of the design of Blue Gene's hardware and software; Need for the supercomputer to evaluate the validity of the so-called force-field models used in computational biology; Contrast of Blue Gene to Deep Blue, the chess-playing supercomputer.